Heat Conductance, a boundary value problem involving certain product of special functions (Global Journal of Science Frontier Research, 2012)
The object of this paper is to discuss an application to certain products containing the H-function of several complex variables in boundary value problems. The results established in this paper are general nature & hence encompass several cases of interest.
Keywords: The product of Fox’s H-function; M-series; a general class of polynomials and the multivariable H-function